John G. Proakis and Dimitris G. Manolakis, Digital signal processing. Principles, algorithms, and aplications : Third edition, 1996, Prentice Hall, New Jersey, USA - Bria, Oscar N. (1999)
This book presents the fundamentals of discrete-time signals, systems, algorithms and applications for students in electrical engineering or computer science. It covers both time-domain and frequency- domain methods for the analysis of linear, discrete-time systems.